CONTRIBUTION OF DECLINE PUSH-UP EXERCISE, HORIZONTAL SWING AND SQUAT-JUMP ON IMPROVING THE RESULTS OF THE O'BRIEN STYLE BULLET THROW FOR EXTRACURRICULAR MALE ATHLETES SENIOR HIGH SCHOOL 2 KISARAN 2015 - Nono Hardinoto; Azwar Lubis (Journal Physical Education, Health and Recreation, 2022)
The low results of athletes' repulsion make the achievement of SMA Negeri 2 Kisaran bullet throw athletes still minimal compared to other athletic numbers. This study aims to find the contribution of decline push-up training, horizontal swing and squat-jump training to improve the results of O'brien style bullet throwing for male extracurricular athletes of SMA Negeri 2 Kisaran in 2015. The research method used in this research is the experimental method, the sample used in this study was 10 people. The research was conducted on 16 October 2015 until 30 November 2015, the statistical calculations used in this study are; Analysis requirements test, Normality test, Bartlet / Homogeneity test and Regression Significance test.The first analysis is that the decline push-up training exercise makes a significant contribution to increasing the results of the O'brien style bullet throw of extracurricular male athletes of SMA Negeri 2 Kisaran 2015, based on the results of the calculation of Fhitung = 8.96 and Ftabel (0.05; 1/8) = 5.32, so that Fhitung> Ftabel with a contribution of 57.76%. Analysis of the second hypothesis, namely, horizontal swing training gives a significant contribution to the improvement of the results of the O'brien style bullet throw of extracurricular male athletes of SMA Negeri 2 Kisaran 2015, based on the results of the calculation of Fhitung = 11.46 and Ftabel (0.05; 1/8) = 5.32, so that Fhitung> Ftabel with a contribution of 59.29%. Analysis of the third hypothesis, namely, squat-jump training gives a significant contribution to the improvement of the results of the O'brien style bullet throw of extracurricular male athletes of SMA Negeri 2 Kisaran 2015, based on the results of the calculation of Fhitung = 5.39 and Ftabel (0.05; 1/8) = 5.32, so that Fhitung> Ftabel with a contribution of 37.21. The analysis of the fourth hypothesis is that the decline push-up, horizontal swing and squat-jump exercises give a significant contribution together to improve the results of the O'brien style bullet throw of extracurricular male athletes of SMA Negeri 2isaran 2015. Based on the calculation of Fhitung> Ftabel = H0 is rejected with a contribution of 89.72%.From hypothesis testing, it can be concluded that; there is a significant contribution of decline push-up, horizontal swing and squat-jump exercises, and there is a significant contribution together from the three forms of training to improve the results of O'Brien style bullet throwing for male extracurricular bullet throwing athletes of SMA Negeri 2 Kisaran 2015.